Evaluation of renal function in subclinical hypothyroidism - Patil, Vijayetha P.; Shilpasree, Alagilwada S.; Patil, Vidya S.; Pravinchandra, Kangokar R.; Ingleshwar, Deepti G.; Vani, Axita C. (Journal of laboratory physicians, 2018)
Abstract INTRODUCTION: Patients with subclinical hypothyroidism (SCH) have a few or no symptoms or signs of thyroid dysfunction and thus by its very nature, SCH is a laboratory diagnosis. Serum creatinine is elevated and glomerular filtration rate (GFR) values are reversibly reduced in overt hypothyroid patients. We hypothesize that SCH also may be associated with low GFR. AIMS AND OBJECTIVES: The objective of this study was (1) to know the effect of SCH on kidney function, (2) to find the correlation between the renal function parameter creatinine, estimated GFR (eGFR), and thyroid-stimulating hormone (TSH), and (3) to know if creatinine values can be predicted by TSH values in SCH cases. MATERIALS AND METHODS: This is a hospital-based cross-sectional study for 1 year. A total of 608 subjects of either sex were included in the study and were divided into 3 groups: (1) SCH, (2) overt hypothyroidism (OHT), and (3) euthyroidism (ET). TSH, free triiodothyronine, free thyroxine, and serum creatinine were estimated and eGFR was calculated using modification of diet in renal disease study equation and the chronic kidney disease epidemiology collaboration equations. RESULTS: Serum creatinine levels were higher and eGFR was lower significantly in the subclinical hypothyroid group when compared to the control ET group ( P < 0.001). The overtly hypothyroid group had significantly higher levels of serum creatinine and lower eGFR when compared to both the groups ( P < 0.001). Significant correlation between TSH, creatinine, and eGFR was found in OHT group only. Linear regression analysis showed the regression in creatinine upon TSH is attributable to 44.5% among OHT group, 48.2% in SCH group. CONCLUSION: It can be concluded that the SCH group behaves biochemically similar to OHT group and changes in serum creatinine reflect tissue hypothyroidism in SCH cases.